Artificial Intelligence Potentialities for Academic Libraries’ Service Delivery: A Literature Review - Mwageni, Rhodes E.; Msonde, Sydney; Ruzegea, Mboni (University of Dar es Salaam Library Journal, 2026)
This paper explores the potential of AI to revolutionise academic library services in Low- and Middle-Income Countries (LMICs). The study employed a thorough literature review to identify and analyse AI tools, such as ChatGPT applications, in academic library services, guided by the Unified Theory of Acceptance and Use of Technology (UTAUT) model. In addition to synthesising the existing literature, this paper proposes a framework for AI integration tailored to the needs and challenges faced by academic libraries in LMICs. The findings reveal both the potential and challenges of adopting AI within HLI in LMICs, identifying gaps in technological infrastructure and specialised skills among library staff. This paper introduces practical recommendations and strategic steps for phased AI adoption in LMIC libraries, including partnership strategies and ethical guidelines. The proposed framework aims to support HLI libraries in gradually integrating AI, ensuring accessibility, inclusivity, and responsible data practices. However, specialised AI skills among librarians remain a core challenge. The study concludes that integrating AI into library frameworks is essential for library professionals to align AI with service delivery and stay current with emerging technologies.